2013
DOI: 10.1590/s0100-29452013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Controle da maturação de caqui 'Fuyu' com aplicação de aminoetoxivinilglicina e 1-metilciclopropeno

Abstract: RESUMO -O armazenamento de caquis é uma ferramenta importante na manutenção da qualidade e no prolongamento da oferta do fruto após a colheita. O objetivo deste trabalho foi avaliar o efeito da aplicação de AVG em pré-colheita, e do 1-MCP, em pré e pós-armazenamento, sobre a manutenção da qualidade pós-colheita e seu efeito na incidência de distúrbios em caquis 'Fuyu' armazenados em atmosfera controlada a -0,5 °C e transferidos a condição de ambiente (20 °C) por 6 dias. Os frutos foram avaliados quanto à quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(7 reference statements)
0
2
1
Order By: Relevance
“…There were no pH differences among all the sorts of crop, with an average value of 5.41. The value obtained for "Fuyu" persimmon fruit (5.33) in this study was lower than the one observed by Brackmann et al (2013) in Rio Grande do Sul, Brazil. The "Rama Forte" persimmon fruit in this study show similar results with the same crops growing in Jundiaí (São Paulo, Brazil) conditions (Mendonça et al, 2015).…”
Section: Yield and Physicochemical Fruit Characteristicscontrasting
confidence: 86%
“…There were no pH differences among all the sorts of crop, with an average value of 5.41. The value obtained for "Fuyu" persimmon fruit (5.33) in this study was lower than the one observed by Brackmann et al (2013) in Rio Grande do Sul, Brazil. The "Rama Forte" persimmon fruit in this study show similar results with the same crops growing in Jundiaí (São Paulo, Brazil) conditions (Mendonça et al, 2015).…”
Section: Yield and Physicochemical Fruit Characteristicscontrasting
confidence: 86%
“…The Brazilian production of persimmons has grown in recent years (Brackmann et al, 2013). However, because the harvest is concentrated in just three months of the year and this fruit is very perishable, this hinders their marketing and consumption throughout the year (Vieites et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Brazilian production of persimmons has grown in recent years, compared to the high yields that this fruit tree provides (Brackmann et al 2013). The state of São Paulo, with more than 8,100 ha in production, has the largest cultivated area in Brazil (Alves et al 2011) and the main persimmons grown are the cultivars 'Rama Forte', 'Mel', 'Guiombo' and'Taubaté' (Pio et al 2003, Tessmer et al 2014).…”
Section: Introductionmentioning
confidence: 99%